Strategi Kampanye Digital : Studi Kasus Pemanfaatan Media Sosial Oleh Kader Muda Perindo - Syallika Nurussyahadah; Adhitya Hafizh Rasyadi; Nia Rafa Ayu; Sagitha Dwi Herliany; Taqya Mafaza (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Advances in information and communication technology, especially social media, have significantly changed the pattern of political communication in the digital era. Social media such as Instagram, X, TikTok, Facebook, and YouTube are now important tools in political campaigns. This research aims to analyze the digital campaign strategy implemented by young cadres of the Indonesian Unity Party (Perindo) in the 2024 elections. The method used is qualitative research with a case study approach, with primary data obtained through in-depth interviews and descriptive data analysis from various sources such as books, articles, and documents. The results showed that Perindo Party's digital campaign strategy in utilizing social media proved effective in increasing public interaction and awareness of their political agenda.